Esteemed colleagues : civility and deliberation in the U.S. Senate - Loomis, Burdett A., 1945-2021. (Washington, D.C. : Brookings Institution Press, 2000)
What's happened to the longstanding traditions of civility and decorum within the world's greatest deliberative body' While the Senate hasn't yet become as rancorous as the House, over the past three decades it has grown noticeably less collegial. In Esteemed Colleagues, leading congressional scholars address the extent to which civility has declined in the U.S. Senate, and how that decline has affected our political system. The contributors analyze the relationships between Senators, shaped by high levels of both individualism and partisanship, and how these ties shape the deliberation of issues before the chamber. Civility and deliberation have changed in recent decades, up to and including the Clinton impeachment process, and the book sheds light on both the current American politics and the broad issues of representation, responsiveness, and capacity within our governmental institutions.
Civility and deliberation : a linked pair? / Burdett A. Loomis -- Part I, Civility in the U.S. Senate. Constitutional cohabitation / Ross K. Baker -- Is the Senate more civil than the House? / Eric M. Uslaner -- Part II, A deliberative institution. Individualism, partisanship, and cooperation in the Senate / Barbara Sinclair -- The procedural context of Senate deliberation / C. Lawrence Evans and Walter J. Oleszek -- Last among equals : the Senate's Presiding Officer / Gerald Gamm and Steven S. Smith -- Part III, Senate deliberation in context. Constituency size and the strategic behavior of Senators / Bruce I. Oppenheimer -- Senators and reporters revisited / Timothy E. Cook -- The Senate and the Executive / Roger H. Davidson and Colton C. Campbell -- Part IV, Civility and deliberation in practice. Civility, deliberation, and impeachment / Norman J. Ornstein -- The Senate Budget Committee: bastion of comity? / James A. Thurber.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: United States. -- Congress. -- Senate; États-Unis. -- Congress. -- Senate; United States. -- Congress. -- Senate; Civil society -- United States; Government etiquette -- United States; Representative government and representation -- United States; Société civile -- États-Unis.; Gouvernement représentatif -- États-Unis.; POLITICAL SCIENCE -- Government -- Legislative Branch; POLITICAL SCIENCE -- American Government -- Legislative Branch; Civil society; Government etiquette; Representative government and representation; United States